Dismantling the Patriarchal Hierarchy in Willa Cather’s A Lost Lady - Ramesh Prasad Adhikary (Journal La Sociale, 2020)
This research paper is focused on how Willa Cather portrays the inner rebellion and the passion of a female character, Marian Forrester in her novel A Lost Lady. She walks against the social norms and she is presented as a rigid character who dismantles the male created hierarchy woman as a subordinate being in the society. Though she is married and living happily with her husband, somewhere deep down in her heart she is not happy with her husband. Marian seems to transcend her husband’s order. At that time female were not allowed to enjoy their freedom like the males. Marian goes against male hegemony and to create her separate identity. As a qualitative research, by using radical feminism as a tool of interpretation, the researcher collected textual evidenced from Cather’s novel and interpreted them to fulfill the objective of this research. This research concludes that Cather’s Marian has dismantled the social hierarchy created by the male superiority or patriarchy in the novel.